What to talk about : on a plane, at a cocktail party, in a tiny elevator with your boss's boss - Colin, Chris, 1975-; Baedecker, Rob. (San Francisco : Chronicle Books, 2014)
"This hilarious yet practical manual written by two comedians tackles the fundamentals of good conversation, offering solid advice and sound social wisdom alongside faux-serious diagrams and inventories of real and humorously implausible scenarios"--
Keywords: Conversation; Conversation -- Humor; HUMOR / Form / Parodies